The Interconnection of Psychology and Forensic Science: Answers from Literature Review - Pandya, Vedant V. (International Journal of Research in Interdisciplinary Studies, 2025)
This paper delivers an in-depth post-doctoral review of the symbiotic relationship between psychology and forensic science. Tracing historical roots from Münsterberg’s early 20th-century experiments to modern neuroscientific and AI-driven approaches, it elucidates how psychological theories and methods underpin critical forensic activities—eyewitness memory enhancement, deception detection, offender profiling, investigative interviewing, risk assessment, and jury decision-making. The review dissects cognitive, social, developmental, personality, and neuropsychological components applied across forensic subfields, examines methodological techniques from laboratory paradigms to virtual reality simulations, and compares international frameworks in North America, Europe, Asia–Pacific, Latin America, and Africa. It assesses contemporary knowledge, identifies key research and practice gaps—ecological validity, cross-cultural generalizability, ethical guidelines—and surveys enabling technologies, including eye-tracking, neuroimaging, statement analysis software, and AI-based deception detectors. Emerging trends, such as trauma-informed interviewing, continuous monitoring of physiological markers, and hybrid human–AI investigative teams, are explored. The paper concludes by proposing a roadmap for future interdisciplinary research, practitioner training, and policy development to strengthen the evidence base at the intersection of psychology and forensic science.